Secondary glaucoma due to progressive iris atrophy – case report - Proniak, Marcin; Gościniewicz, Piotr; Mrukwa-Kominek, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica, 2023)
Iridocorneal endothelial syndrome is a rare disease, the etiology of which is not clearly understood. It usually manifests in only one eye, causing corneal edema, secondary glaucoma, and iris anomalies. Depending on the occurrence of these symptoms, three different variants of the condition can be distinguished: Chandler syndrome, Cogan-Reese syndrome, and progressive iris atrophy. We present a case report of a female patient with secondary glaucoma due to progressive iris atrophy, who underwent transscleral ciliary body treatment to reduce and stabilize intraocular pressure.